Dissociation between Conceptual and Perceptual Implicit Memory: Evidence from Patients with Frontal and Occipital Lobe Lesions - Gong, Liang; Wang, JiHua; Yang, XuDong; Feng, Lei; Li, Xiu; Gu, Cui; Wang, MeiHong; Hu, JiaYun; Cheng, Huaidong (Frontiers in Human Neuroscience, 2016)
The latest neuroimaging studies about implicit memory have revealed that different implicit memory types may be processed by different parts of the brain. However, studies have rarely examined what subtypes of implicit memory processes are affected in patients with various brain-injuries. Twenty patients with frontal lobe injury, 25 patients with occipital lobe injury, and 29 healthy controls were recruited for the study. Two subtypes of implicit memory were investigated by using structurally parallel perceptual (picture identification task) and conceptual (category exemplar generation task) implicit memory tests in the three groups, as well as explicit memory tests. The results indicated that the priming of conceptual implicit memory and explicit memory tasks in patients with frontal lobe injury was poorer than that observed in healthy controls, while perceptual implicit memory was identical between the two groups. In contrast, the priming of perceptual implicit memory in patients with occipital lobe injury was poorer than that in healthy controls, while the priming of conceptual implicit memory and explicit memory was similar to that in healthy controls. This double dissociation between perceptual and conceptual implicit memory across the brain areas implies that occipital lobes may participate in perceptual implicit memory, while frontal lobes may be involved in processing conceptual memory.